Предмет:
МатематикаАвтор:
анонимsin (4 * x) - sin (2 * x) = sin x;
Упростим уравнение.
2 * sin ((4 * x - 2 * x)/2) * cos ((4 * x + 2 * x)/2) = sin x;
2 * sin (2 * x/2) * cos (6 * x/2) = sin x;
2 * sin x * cos (3 * x) = sin x;
2 * sin x * cos (3 * x) - sin x = 0;
Вынесем за скобки общий множитель.
sin x * (2 * cos (3 * x) - 1) = 0;
1) sin x = 0;
x = пи * n, n ∈ Z;
2) 2 * cos (3 * x) - 1 = 0;
2 * cos (3 * x) = 1;
cos (3 * x) = 1/2;
3 * x = +-arccos (1/2) + пи * n, n ∈ Z;
3 * x = +-пи/3 + пи * n, n ∈ Z;
x = +-пи/3 * 1/3 + 1/3 * пи * n, n ∈ Z;
x = +-пи/9 + пи/3 * n, n ∈ Z.
Автор:
guerrero85Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть